ChemInform Abstract: Synthesis, Structural, and Transport Properties of Cr‐Doped BaTi2As2O. Issue 10 (March 2015) - Mu, Gang; et al., et al.
Abstract Cr‐doped BaTi2‐xCrxAs2O (x = 0—0.154) is synthesized by solid state reaction of stoichiometric mixtures of CrAs (obtained from Cr and As at 700 °C for 20 h), BaO, Ti, and As (950 °C, 5 d).